GE_GERICHTE P/5706/2008 vom 5. September 2008 - GE Cour de justice (2008)
; COMMERCE DE STUPÉFIANTS ; CONCOURS D'INFRACTIONS ; SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE | CP.47; CP.49; 1; CP.42; CP.43; LStup. 19.2a.19.1.2 CP.252 LEtr.115.1 LCR.95.1